The corporate social responsibility of Port of Tanjung Pelepas activities from the local communities’ perspectives / Nur Suriatie Md. Zamri - Md. Zamri, Nur Suriatie (Faculty of Business and Management, 2008)
This report examines the issue the PTP’s Corporate Social Responsibility Activities from The Perspectives of Local Communities. Corporate Social Responsibility is the evolution of the relationship between companies and society has been one of slow transformation from a philanthropic coexistence to one where the mutual interest of all stakeholder groups including employees, customers, suppliers, investors and the local community is gaining paramount importance.